A historical analysis of the criminalization of self-abortion in Brazil (1890-1940): from medical speeches to criminological positivism - Cunha, Bárbara Madruga da (Em Perspectiva, 2019)
The Penal Code of 1890 was the first to criminalize the self-abortion. Although there are no studies in the legal area that seek to verify the reasons why the legislator chose to typify this conduct, there are researches that demonstrate the existence of a strong performance of the medical profession in favor of the criminalization of self abortion as a form of control of sexuality feminine. On the other hand, in the end of the nineteenth century, there was an approximation between law and medicine, through the rise of criminological positivism. With this in view, this article proposes to analyze the doctrine of three Brazilian jurists affiliated to the Italian Positive School - João Vieira Araújo (1902), Oscar Macedo Soares (1910) and Galdino Siqueira (1932), in order to verify the presence of medical discourse in their comments on the crime of abortion. To do this, we will initially do a bibliographical review of the researches that demonstrate the medical practice in favor of the criminalization of abortion, then we will analyze how the crime is approached in the work of Lombroso and Ferrero, "Criminal Woman, the Prostitute, and the Normal Woman" ( 1893), to finally examine the national doctrine.